Improving access block in emergency department: An audit cycle - Rijal, Suraj; Adhikari, Sunil (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Introduction: Emergency department crowding is a major problem worldwide and has been associated with a variety of deleterious patient care and outcomes. Crowding has also been implicated in increased work load, burnout and staff turnover. ED is the common entry point to hospitals for nearly all patients with acute problems. Prolonged length of ED stay is the most common cause of patient dissatisfaction. Method: Plan-Do-Study-Act (PDSA) cycle will be used. The barrier identified for first cycle was delay in access is due to delay in consultation, evaluation by admission team, and delay in transfer of patient to ward. There are two cycles of data collections. In first cycle. we identified a barrier and set an indicator to measure it. We did a first cycle, analysed and evaluated the data and did necessary interventions. Then did second cycle to see the improvement and consistency for various departments. Result: In first cycle, average of length of overall ED stay of all admitted patients is 401.95mins (Median time-368.5min). Total numbers of patients analyzed were 165. 63.63% of patients were transferred to respected admitting departments within 8 hours of ED stay. In second cycle, average of length of overall ED stay of all admitted patients is 375. 01mins (median time-341.5min). Total patient analyzed were 161. 67.5% of patients were transferred to respected admitting departments within 8 hours of ED stay. Conclusion: Delay in access is due to delay in consultation, evaluation by admission team, and delay in transfer of patient to ward.